The Impact of Strategic Mind on Social Responsibility - An Analytical Study in Dhi Qar Oil Company - Yasir Taher*, Ammar; Zahim Faisal, Muthanna (Journal of Economics and Administrative Sciences, 2024)
Purpose: The aim of the research is to activate the influence of strategic mind to enhance the principle of social responsibility in Dhi Qar Oil Company. Theoretical Framework: Recent literature indicates a growing trend towards applying the principle of social responsibility, transforming it into a competitive strategy among organizations, especially when possessing strategic mind to devise implementation steps (Khouj, 2020:84). Design/Methodology/Approach:We analyzed the literature and activities advocating for the implementation of the principle of social responsibility using the scale (Schwartz & Carroll, 2003:67) in various organizations. We also examined the impact of possessing a strategic mindset, as measured by (Pisapia et al., 2005:60), on achieving desired outcomes through local, regional, and international research and studies in this regard. Results: The research findings indicate a significant direct positive relationship between strategic mind and social responsibility overall, particularly concerning the economic dimension. A set of recommendations was provided to rectify the nature of these variables in practice, in line with research trends. Research, Practical & Social implications: We propose that organizations integrate the implementation of the principle of responsibility into their future strategies, considering it a competitive advantage to be achieved. Originality/value: The results indicate that the application of the principle of social responsibility has begun to be implemented in organizations, especially those with a strategic vision derived from their strategic mind leaders, achieving levels of satisfaction and approval from stakeholders. Research Type: Research Paper